Early Antiretroviral Therapy for Simian Immunodeficiency Virus Infection Leads to Mucosal CD4(+) T-Cell Restoration and Enhanced Gene Expression Regulating Mucosal Repair and Regeneration - George, Michael D. (American Society for Microbiology, 2005)
Simian immunodeficiency virus (SIV) and human immunodeficiency virus (HIV) infections lead to rapid depletion of CD4(+) T cells from gut-associated lymphoid tissue (GALT). Although the administration of antiretroviral therapy (ART) has been shown to increase CD4(+) T-cell levels in the peripheral blood in both SIV and HIV infections, its efficacy in restoring intestinal mucosal CD4(+) T cells has not been well investigated. To gain insights into the molecular mechanisms of virally induced disruptions in the mucosal immune system, we have evaluated longitudinal changes in viral burden, T-cell subsets, and mucosal gene expression profiles in SIV-infected rhesus macaques in the absence or presence of ART. Our results demonstrate a dramatic suppression of mucosal viral loads and rapid reconstitution of CD4(+) T cells in GALT in animals receiving ART that were not observed in untreated SIV-infected animals. DNA microarray-based gene expression profiling indicated that CD4(+) T-cell restoration in GALT was associated with up regulation of growth factors and genes involved in repair and regeneration of the mucosal epithelium. In contrast, untreated SIV-infected animals increased expression of lymphocyte activation and inflammatory response-associated genes and did not up regulate mucosal growth and repair associated transcription. In conclusion, these data indicate that initiating ART in primary SIV infection may lead to the restoration of the mucosal immune system through reduction of inflammation and promotion of epithelial repair in the intestinal mucosa.